Response of Muhammadiyah to the World of Education: History and Recent Developments - Nikmah, Shobriyah; Nurhakim, Moh. (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
This research aimed to determine the response of Muhammadiyah to the actual issues that focused on educational development and historical flashbacks. The method used was qualitative by collecting the data by using library research. The findings in this research contained the response of Muhammadiyah to educational development which focused on innovation, the quality of institutions improvement, human resources development and the beginnings or history of education itself. Before education in Muhammadiyah experienced its current extraordinary development, the education in the past time was only carried out in the mosques. The Dutch colonies forbade indigenous Indonesian people to pursue general education. Based on its history, education at Muhammadiyah was divided into several periods, namely the pioneering, development and transformation periods. Nowadays, Muhammadiyah has developed very well. There are roles of Muhammadiyah in education itself, namely by building Muhammadiyah schools and universities as widely as possible and providing various kinds of scholarships so that education is more equitable, improving the quality of teachers who not only teach worldly things but are balanced towards Hablumminallah. Muhammadiyah even provides grants for research to lecturer or student.